PROSES PEMBELAJARAN PENDIDIKAN ANAK USIA DINI BERBASIS PENDEKATAN KI HAJAR DEWANTARA - Srie Kusuma Wardhani Ni Ketut (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2021)
Early childhood education is actually a shared responsibility between families, communities and governments. School as a continuation of education in the family, because the first and foremost education children get is in the family. The family as the smallest social unit is the most important and first educational environment, in the sense that the family is the environment most responsible for educating their children. The education provided by parents should provide the basis for education, the socialization process and life in society. According to Ki Hadjar Dewantara, the Among system is a method of learning and education based on care and dedication based on love. The among system is explained in three sentences as follows: Ing ngarso sing tulodo, Ing madya mangun karso, Tut wuri handayani, The among system is very suitable to be applied to children who have entered elementary school education between grades 1 to grade 3. because at this stage the child must be motivated and aroused the will so that the child is encouraged to be independent. This concept can also be used in building self-confidence and character building for children.